Close the ring to break the cycle: tandem quinolone-alkyne-cyclisation gives access to tricyclic pyrrolo[1, 2-a]quinolin-5-ones with potent anti-protozoal activity. Issue 49 (23rd May 2019) - Szamosvári, Dávid; Sylvester, Kayla; Schmid, Philipp; Lu, Kuan-Yi; Derbyshire, Emily R.; Böttcher, Thomas
Abstract : We describe a tandem reaction leading to tricyclic pyrrolo[1, 2- a ]quinolin-5-ones with unique selectivity against the liver stage of the malaria parasite. Abstract : Expanding the chemical space of quinolones led to a tandem quinolone-alkyne-cyclisation reaction allowing chemoselective control of the synthesis of tricyclic pyrrolo[1, 2- a ]quinolin-5-ones. Importantly, we discovered anti-protozoal activity against Plasmodium and Toxoplasma with specific potency of one of the compounds against the liver stage of the malaria parasite in the nanomolar range.